Analisis Linguistik Forensik sebagai Alat Bukti dalam Kasus Cyberbullying oleh Generasi Z: Perspektif Literasi Hukum - Joharsah Joharsah; Rika Kartika; Diah Kusyani (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to explore the strategic role of forensic linguistics as a scientific tool for evidentiary analysis in cyberbullying cases involving Generation Z, while also examining the correlation between digital legal literacy and their engagement in online hate speech. Employing a qualitative methodology with a descriptive-analytic approach, this research integrates multimodal data sources: digital text analysis from social media platforms (TikTok, Instagram, and Facebook), in-depth interviews with legal and linguistic experts, and a structured survey involving 75 Generation Z respondents. The results demonstrate that cyberbullying discourse is predominantly manifested through forms such as sarcasm, body shaming, covert threats, and discriminatory labeling—often disguised within colloquial digital expressions. Forensic linguistic analysis proves instrumental in identifying latent illocutionary acts and semantic-pragmatic structures that constitute violations under the Indonesian Electronic Information and Transactions Law (UU ITE). The findings further reveal that a significant proportion of Generation Z lacks foundational knowledge of digital legal norms, thereby increasing their vulnerability to either perpetrating or tolerating cyberbullying. This study proposes a three-pillar model of digital legal literacy—comprising the identification of unlawful expressions, comprehension of digital legal frameworks, and practical reporting competence—as a preventative educational framework. The research highlights the necessity for interdisciplinary collaboration between linguists, legal practitioners, and educators to address language-based cybercrimes in an increasingly digitized society.